Legal Protection for Taxpayers in Tax Disputes in Court - Salwa Khairina Azzahra; Nabila Hilmy Khairunnisa Hasibuan; Amanda Putri Fajrin; Nadiatul Maghfirah; Laila Rizqillah (ISNU Nine-Star Multidisciplinary Journal, 2025)
Tax disputes in Indonesia often pose challenges for taxpayers to obtain fair legal protection in the Tax Court. This research aims to analyze the legal protection mechanism for taxpayers, identify obstacles to its implementation, and propose reforms to improve justice and legal certainty. Using a normative vuridis approach with qualitative analysis. This research examines laws and regulations, court decisions, and tax law literature. The results of the study show that the Tax Court provides protection through objection, appeal, and review procedures, supported by the principles of transparency and judicial independence. However, high litigation costs, inconsistencies in judgments, low legal literacy, and complex administrative procedures hinder the effectiveness of protection, especially for small taxpayers. Reforms such as digitization of court processes, legal education, harmonization, judgment, and mediation are proposed to address these constraints, The study concludes that although, the legal framework has been robust, more inclusive and efficient implementation is needed to ensure fairness for all taxpayers, Recommendations include digital platforms for easier access and educational programs to improve taxpayer understanding.